Trade Policy and Resource Allocation in the Presence of Product Differentiation - de Melo, Jaime; Robinson, Sherman (The Review of Economics and Statistics, 1981)
Traditionally, the empirical analysis of the effects of trade policy on resource allocation has relied both on a partial equilibrium framework using effective rates of protection and on a multisector general equilibrium framework. This paper responds to the growing dissatisfaction with the concept of perfect substitutability that has been assumed in these models. It discusses the theorectical properties and implications of one practical specification of product differentation and explores quantitatively the impact of trade policy on relative prices and resource pulls with a general equilibrium model that incorporates product differentiation. An analysis of the implications of product differentation for the autonomy of the domestic price system is extended to include intermediate products. The specification of imperfect substitutability provides a practical way of capturing product differentation both in a partial equilibrium and in a general equilibrium model. However, partial equilibrium based estimates are not likely to be robust when there are substantial policy changes that affect a number of sectors simultaneously.